ESGO/ESTRO/ESP Guidelines for the management of patients with cervical cancer – Update 2023 - Cibula, David (2023)
Funding Information: The authors thank ESGO, ESTRO, and ESP for their support. The authors also thank the 155 international reviewers (physicians and patient representatives, see Appendix 2 in Online Supplemental File 2) for their valuable comments and suggestions. The authors thank the ESGO office, especially Kamila Macku, Tereza Cicakova, and Kateřina Šibravová, provided invaluable logistical and administrative support throughout the process. The development group (including all authors) is collectively responsible for the decision to submit for publication. DC (chair), JL (chair), MRR (chair) and FP (methodologist) wrote the first draft of the manuscript. All other contributors have actively given personal input, reviewed the manuscript, and have given final approval before submission. DC is responsible for the overall content as the guarantor. Initiated through the ESGO the decision to develop multidisciplinary guidelines was made jointly by the ESGO, ESTRO, and ESP. The ESGO provided administrative support. The ESGO, ESTRO and ESP are nonprofit knowledgeable societies. *These guidelines were developed by ESGO, ESTRO and ESP and are published in the Int J Gynecol Cancer, Radiother Oncol and Virchows Archiv. CCh has reported advisory boards for GSK, MSD and EISAI; SFL has reported advisory boards for MSD, GSK, AstraZeneca and Novartis; DL has reported consultant honoria from AstraZeneca, Clovis Oncology, GSK, MSD, Immunogen, Genmab, Amgen, Seagen and PharmaMar, advisory boards for AstraZeneca, Merck Serono, Seagen, Immunogen, Genmab, Oncoinvest, Corcept and Sutro, research institutional funding from Clovis Oncology, GSK, MSD and PharmaMar, research sponsored by AstraZeneca, Clovis Oncology, Genmab, GSK, Immunogen, Incyte, MSD, Roche, Seagen and Novartis, and speakers’ bureau activities for AstraZeneca, Clovis Oncology, GSK, MSD and PharmaMar; UM has reported advisory boards for AstraZeneca (Steering committee member for CALLA Study); RN has reported research grants from Elekta, Varian, Accuray, Dutch Research Council, and Dutch Cancer Society; AO has reported personal fees for advisory board membersip from Agenus, AstraZeneca, Clovis Oncology, Corcept Therapeutics, Deciphera Pharmaceuticals, Eisai, EMD Serono, F. Hoffmann-La Roche, Genmab/Seagen, GSK, ImmunoGen, Itheos, Merck Sharp & Dohme de Espana, SA, Mersana Thereapeutics, Novocure, PharmaMar, piIME Oncology, Roche, Sattucklabs, Sutro Biopharma and Tesaro, and personal fees for travel/accomodation from AstraZeneca, PharmaMar and Roche; DQ has reported advisory boards for Mimark inc; MPS has reported research grants and personal fees for workshops from Elekta AB; DC, MRR, FP, CC, AF, DF, DJK, FJ, CK, PM, RN, FPec, JP, SR, AS, VS, KT, IZ and JCL have reported no conflicts of interest. Not commissioned; internally peer reviewed. Not applicable. Not applicable. David Cibula, Maria Rosaria Raspollini, François Planchamp, Carlos Centeno, Cyrus Chargari, Ana Felix, Daniela Fischerova, Daniela Jahn-Kuch, Florence Joly, Christhardt Kohler, Sigurd F. Lax, Domenica Lorusso, Umesh Mahantshetty, Patrice Mathevet, Raj Naik, Remi Nout, Ana Oaknin, Fedro Peccatori, Jan Persson, Denis Querleu, Sandra Rubio, Maximilian Paul Schmid, Artem Stepanyan, Valentyn Svintsitskyi, Karl Tamussino, Ignacio Zapardiel, Jacob Christian Lindegaard. All data relevant to the study are included in the article or uploaded as supplementary information. Funding Information: CCh has reported advisory boards for GSK, MSD and EISAI; SFL has reported advisory boards for MSD, GSK, AstraZeneca and Novartis; DL has reported consultant honoria from AstraZeneca, Clovis Oncology, GSK, MSD, Immunogen, Genmab, Amgen, Seagen and PharmaMar, advisory boards for AstraZeneca, Merck Serono, Seagen, Immunogen, Genmab, Oncoinvest, Corcept and Sutro, research institutional funding from Clovis Oncology, GSK, MSD and PharmaMar, research sponsored by AstraZeneca, Clovis Oncology, Genmab, GSK, Immunogen, Incyte, MSD, Roche, Seagen and Novartis, and speakers’ bureau activities for AstraZeneca, Clovis Oncology, GSK, MSD and PharmaMar; UM has reported advisory boards for AstraZeneca (Steering committee member for CALLA Study); RN has reported research grants from Elekta, Varian, Accuray, Dutch Research Council, and Dutch Cancer Society; AO has reported personal fees for advisory board membersip from Agenus, AstraZeneca, Clovis Oncology, Corcept Therapeutics, Deciphera Pharmaceuticals, Eisai, EMD Serono, F. Hoffmann-La Roche, Genmab/Seagen, GSK, ImmunoGen, Itheos, Merck Sharp & Dohme de Espana, SA, Mersana Thereapeutics, Novocure, PharmaMar, piIME Oncology, Roche, Sattucklabs, Sutro Biopharma and Tesaro, and personal fees for travel/accomodation from AstraZeneca, PharmaMar and Roche; DQ has reported advisory boards for Mimark inc; MPS has reported research grants and personal fees for workshops from Elekta AB; DC, MRR, FP, CC, AF, DF, DJK, FJ, CK, PM, RN, FPec, JP, SR, AS, VS, KT, IZ and JCL have reported no conflicts of interest. Publisher Copyright: © 2023 ESGO, ESTRO, ESP